Current Pharmacological Trends on Myricetin - Gupta, Gudiya; Siddiqui, Mohd Aftab; Khan, Mohd Muazzam; Ajmal, Mohd; Ahsan, Rabiya; Rahaman, Md Azizur; Ahmad, Md Afroz; Arshad, Md; Khushtar, Mohammad (Drug Research, 2020)
Myricetin is a member of the group of ﬂavonoids called ﬂavonols. Myricetin is obtained from various fruit, vegetables, tea, berries and red wine. Myricetin is characterized by the pysrogallol B-ring, and the more hydroxylated structure is known to be capable for its increased biological properties compared with other ﬂavonols. Myricetin is produced by the Myricaceae, Anacardiaceae, Polygonaceae, Pinaceae and Primulacea families. It is soluble in organic solvent such as ethanol, DMSO (dimethyl sulfoxide), and dimethyl formamide (DMF). It is sparingly soluble in aqueous buffers. Myricetin shows its various pharmacological activities including antioxidant, anti-amyloidogenic, antibacterial, antiviral, antidiabetic, anticancer, anti-inﬂammatory, anti-epileptic and anti-ulcer. This review article focuses on pharmacological effects of Myricetin on different diseases such as osteoporotic disorder, anti-inflammatory disorder, alzheimer’s disease, anti-epileptic, cancer, cardiac disorder, diabetic metabolic disorder, hepatoprotective disorder and gastro protective disorder.
Keywords: antioxidants/NO pathways drugs; behavioural pharmacology; toxicology; cardiovascular pharmacology; cancer pharmacology; cancer